التدريبات في كتاب تعليم اللغة العربية للصف الثالث المتوسط بوزارة الشؤون الدينية الإندونيسية عام 2020 - Siti Desi Hidayati; Evi Hulwati; Ummi Mufida (UIN Fatmawati Sukarno Bengkulu, 2022)
One of the elements of learning Arabic in Indonesia is a book, this book is issued by the Ministry of Religion. It includes exercises that act as evaluations of learning and reinforcement of what students have learned. Because of the importance of an exercise in the textbook, this study aims to find out the various forms of practice questions in the Arabic language learning book and to find out the analysis of the practice questions in it based on theoretical validity. The researcher conducted research using a qualitative approach and also used a descriptive literature analysis method, in which the researcher researched researched the analysis of Arab language books for grade 3 MTS Ministry of Religion in 2020 as an analytical study. One of the important points from the results of this study is that there are various forms of practice, from essay questions and objective questions to all of them except matching in the various forms of thematic questions.